Telecommunication, Socioeconomic, and Financial Inclusion : An Empirical Evidence from Bihar - Siddiqui, Taufeeque Ahmad; Siddiqui, Kashif Iqbal (Prabandhan: Indian Journal of Management, 2020)
This article aimed to examine the relationship between determinants of telecommunication, socioeconomic variables, and financial inclusion in India. The current study adopted a cross-sectional design and quantitative approach. A sample of 400 was randomly drawn using a predetermined schedule from the adult individuals of two villages of Madhubani district of Bihar. The randomly selected villages are Chaparia and Jagatpur of Madhubani district. The three dimensions considered for the study are financial inclusion, telecommunication, and socioeconomic factors. SmartPLS was used to establish the hypothesized relationship between telecommunication, socioeconomic, and financial inclusion. The impact of telecommunication and socioeconomic constructs on financial inclusion was evident from the current study in several constructs. Out of 18 paths, 12 paths were significant at a 5% significance level, and three paths were significant at a 10% significance level. The results are vital for policymakers. Fintech innovation and revolution are a vivacious tool to achieve financial inclusion by including the financially excluded sections. The financial institutions may tie-up with the telecom companies to make them their channel partners.